2011
DOI: 10.3233/jad-2010-101254
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 mRNA Expression in Alzheimer's Disease Postmortem Brain Tissue

Abstract: β-site AβPP cleaving enzyme 1 (BACE1) catalyses the rate-limiting step for production of amyloid-β (Aβ) peptides, involved in the pathological cascade underlying Alzheimer's disease (AD). Elevated BACE1 protein levels and activity have been reported in AD postmortem brains. Our study explored whether this was due to elevated BACE1 mRNA expression. RNA was prepared from five brain regions in three study groups: controls, individuals with AD, and another neurodegenerative disease group affected by either Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 0 publications
3
31
0
2
Order By: Relevance
“…In addition, we observed a significant increase in BACE1 expression in AD subjects as compared with healthy controls (Fig. 7a and c), which is consistent with previous studies showing elevated levels of BACE1 mRNA (Coulson et al, 2010) and protein (Fukumoto et al, 2002; Harada et al, 2006; Holsinger et al, 2002; Li et al, 2004; Tyler et al, 2002; Yang et al, 2003) in the AD brain. Total PACS1 levels were not significantly changed (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In addition, we observed a significant increase in BACE1 expression in AD subjects as compared with healthy controls (Fig. 7a and c), which is consistent with previous studies showing elevated levels of BACE1 mRNA (Coulson et al, 2010) and protein (Fukumoto et al, 2002; Harada et al, 2006; Holsinger et al, 2002; Li et al, 2004; Tyler et al, 2002; Yang et al, 2003) in the AD brain. Total PACS1 levels were not significantly changed (Fig.…”
Section: Resultssupporting
confidence: 92%
“…RNA is assumed to degrade from a 5 0 to 3 0 direction but in vivo this might be a more haphazard process with involvement of 3 0 -5 0 exonucleases and endonucleases. Even in the absence of 3 0 directed degradation, oligo dT-primed cDNA could still bias particular assays targeting longer transcripts with 5 0 amplicon locations [52]. However, we saw no relationship between either the transcript length, or amplicon position, and the strength of correlations with RIN across the nine transcripts assayed.…”
Section: Strengths and Weaknessesmentioning
confidence: 79%
“…The level of BACE1 in AD pathology is still in argument. Some studies reported that the level of BACE1 was elevated in sporadic AD [1,28], while other investigations showed no obvious changes in mRNA level in spite of the increased BACE1 activity and protein level [20,29,30]. The potential mechanism still needs to be explored.…”
Section: Discussionmentioning
confidence: 97%